Pengembangan Sistem Survei Kepuasan Pelanggan Pada PDAM Surya Sembada Kota Surabaya - Alfa Nur Fitriana Islami; Ismiarta Aknuranda; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
PDAM Surya Sembada Kota Surabaya is one of regional owned business unit which has responsibility in providing drinking water for Surabaya and its surrounding community. Therefore, PDAM conducts customer satisfaction surveys every year to improve the quality of service e in the company in order to foster satisfaction for its customers. In the process of implementing the customer satisfaction survey, PDAM experienced several obstacles such as in determining the sample data for survey respondents who still use manual calculations resulted in frequent miscalculation and input data, then in terms of cost PDAM have to incur additional costs because it uses the services of survey providers to distributing questionnaires and analyzing the results of questionnaires. The distribution of questionnaires is still done manually so that PDAM still have to provide questionnaire question in paper form. The distribution of questionnaires and analysis carried out by the survey service providers resulted in the large number of data manipulations. Based on the above problems, the solution that can be applied is to develop a computer-based customer satisfaction survey system that can assist in processing sample data, delivering effective and efficient questionnaires, and can provide reports of questionnaire analysis results quickly and accurately. The method used in the development is the waterfall method with the stages of requirements analysis, design, implementation and testing. System testing process using validation testing and compatibility testing. The results of the validation tests show the overall functional requirements can run well in accordance with the needs of users. And the results of compatibility testing show that the system works well on some different browsers.